Aggregated structure of flocculated asphaltenes - Savvidis, Theophylaktos G.; Fenistein, Denis; Barré, LoïC; Béhar, Emmanuel (AIChE journal, 2001)
Many petroleum processing problems are related to asphaltene flocculation. A detailed understanding of the colloidal structure of asphaltenes in oild can play a decisive role in improving processing facilities and/or operating conditions. The structure of the flocculated part of the asphaltenes of a crude oil far above the flocculation threshold was studied to understand its links with macroscopic phase separation. Asphaltene filtrations were performed using filter pore sizes from 0.025 to 10 μm. According to small angle X‐ray scattering (SAXS) spectra and density measurements, these extracted asphaltenes in toluene solutions did not have any physical differences. Measurements of nanometric sizes for the dispersed particles after dissolution in toluene show that micron‐size flocculated asphaltenes are strongly aggregated structures. Therefore, filtration experiments separate asphaltenes corresponding powders show spherically shaped aggregates of micron size. SAXS and USAXS techniques were used to investigate the internal structure of the asphaltene powder. The aggregates are clearly a compact organization of asphaltenic material. This dense structure explains why flocculated asphaltenes are subject to sedimentation, which induces the visible macroscopic phase separation.